1994
DOI: 10.1136/qshc.3.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Views of survivors of stroke on benefits of physiotherapy.

Abstract: Objective-To describe the components of physiotherapy valued by survivors of a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
6

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 10 publications
1
62
0
6
Order By: Relevance
“…Participants in this study identified a number of sources of hope -family, friends, healthcare providers and other patients which is consistent with the hope literature (Arnaert, et al, 2006;Barker & Brauer, 2005;Bays, 2001;Jones, et al, 2008;Popovich, et al, 2007;Pound, et al, 1994). This is supported by Green and Waks (2008); Christopher Green reported meeting another person with aphasia was important in helping him feel there was hope for his situation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Participants in this study identified a number of sources of hope -family, friends, healthcare providers and other patients which is consistent with the hope literature (Arnaert, et al, 2006;Barker & Brauer, 2005;Bays, 2001;Jones, et al, 2008;Popovich, et al, 2007;Pound, et al, 1994). This is supported by Green and Waks (2008); Christopher Green reported meeting another person with aphasia was important in helping him feel there was hope for his situation.…”
Section: Discussionsupporting
confidence: 60%
“…Levels of hope could fluctuate following stroke (Cross & Schneider, 2010;Jones, et al, 2008) and could co-exist with emotions such as worry, uncertainty and fear (Arnaert, et al, 2006;Folden, 1994;Jones, et al, 2008). Hope could be developed and maintained through internal factors such as personal attitude, progress to date and stroke severity (Arnaert, et al, 2006;Barker & Brauer, 2005;Bays, 2001;Cross & Schneider, 2010;Dowswell, et al, 2002;Jones, et al, 2008;Nilsson, Jansson, & Norberg, 1997;Popovich, Fox, & Bandagi, 2007;Pound, Bury, Gompertz, & Ebrahim, 1994) and external factors such as social connections, spiritual sources and healthcare professionals (Arnaert, et al, 2006;Barker & Brauer, 2005;Bays, 2001;Cross & Schneider, 2010;Jones, et al, 2008;Popovich, et al, 2007;Pound, et al, 1994). Hope was generally considered a positive construct, a source of motivation (Arnaert, et al, 2006;Cross & Schneider, 2010) that could help modulate mood, adjustment and ability to think about the future (Barker & Brauer, 2005;Jones, et al, 2008;White, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The association between increased satisfaction and increased support from community services makes sense intuitively, but the relationship between satisfaction and the amount of therapy is more complex. People with stroke often give the impression that they never want therapy to stop, 17 yet while an increase in therapy was positively associated with satisfaction among the patients in this sample, they also indicated a ceiling for the amount of therapy they appreciated. Further, qualitative research is necessary to investigate why this might be.…”
Section: Resultsmentioning
confidence: 94%
“…An early sociological study investigated how people with stroke disability adapt in light of societal expectations and norms, arguing that rehabilitation seeks to teach patients to redefine stroke as an inconvenience that can be overcome through new techniques. 39 Findings from a UK study indicated that physiotherapy was valued because it was felt to lead directly to functional recovery, 40 while a US study identified a failure to meet individual needs or to facilitate the transition to life at home. 41 Only one study, conducted in Hong Kong, aimed specifically to allow patients to identify their own rehabilitation needs.…”
Section: Rehabilitation Therapiesmentioning
confidence: 99%